Scene from Krishna’s childhood when his mother, Yashoda tied him to the milk churn while she was working in the kitchen. Krishna crawled across the courtyard dragging the churn, which got stuck between two big trees and on a pull by Krishna, the trees crashed down! - Brig. Ajai Singh (2021)
Image courtesy: Brig A.P. Singh - www.collectingmoments.in